CHARACTERISTICS OF SOCIAL CAPITAL AGRIBUSINESS MICRO FINANCIAL INSTITUTIONS OF AGRIBUSINESS (MFIA) IN PADANG CITY - Devi Analia; Cipta Budiman; Syahyana Raesi; Rika Hariance (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
The role of social capital in micro-small businesses is very important, especially in Agribusiness Micro Finance Institutions (MFIA). The presence of this LKMA can help small businesses to gain access to better financial services with easier requirements. This study aims to describe how the characteristics of social capital contained in Microfinance Institution of Agribusiness (MFIA). The research was conducted at LKMA in Padang City. The sampling technique used is purposive sampling, namely MFIA whose status is active, legally incorporated and Financial Services Authority (OJK). Data were obtained from two MFIA, namely MFIA Saiyo Sakato in Padang Besi District and MFIA Mutiara Sejati in Koto Tangah District. The research method used was descriptive qualitative by using scoring on aspects of social capital. The results show that the social capital contained in MFIA were aspects of trust, network and norms. The existence and sustainability of LKMA was based on the strength of trust that was built between the management of MFIA and members of MFIA The aspect of network strength that supports the development of MFIA was that its members were scattered in every kelurahan in Padang City. The aspect of social norms that support the sustainability of the MFIA. From the results of this study it is hoped that the power of social capital has a good impact on the sustainability of the agribusiness microfinance institution (MFIA).